Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen (Studi Kasus Pada Jemblung Coffee Ii Malang) - Mohammad Lutfi; Rois Arifin; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research seeks the influence of product quality and price on customer satisfaction in Jemblung II Malang coffee. This type of research uses quantitative methods that aim to find significant influences partially and simultaneously. The number of respondents used was 60 respondents, with the criteria of consumers aged 17 years and above and consumers who made coffee purchases. This research method is tested by validity and reliability tests. The classic assumption tests used are the normality assumption test, the multicolonierity assumption test, and the heterokedastisity assumption test. In addition, several linear regression tests are also used, and hypothesis testing, namely F test, T test, and determination test (R2). The results of this study show that there is a significant influence simultaneously between product quality variables and prices on consumer satisfaction. In part, there is an influence on product quality affecting consumer satisfaction, and price has a significant effect on consumer satisfaction. Price is the most dominant variable in consumer satisfaction for coffee jemblung II Malang. Keywords: Product Quality, Price, Customer Satisfaction